Checklist of the Odonata (Insecta) of Sundaland and Wallacea (Malaysia, Singapore, Brunei, Indonesia and Timor Leste) - Rory A., Dow; Choong, C. Y.; Jongkar, Grinang; P., Lupiyaningdya; Robin W.J., Ngiam; V. J., Kalkman (Magnolia Press, 2024)
A checklist, based on a database containing published data, of the Odonata (dragonflies and damselflies) occurring in Sundaland and wallacea is presented. The presence of (sub)species is indicated for eight main regions (Singapore & Peninsular Malaysia, South China Sea (islands in the South China Sea that are not sensibly treated as satellites of larger landmasses), Borneo, Sumatra, Java & Bali, Lesser Sunda, Sulawesi, Moluccas), 22 subregions and 80 smaller islands and island groups. In total 743 full species are recorded from the entire area with 549 species known from Sundaland and 270 from wallacea. Of these 482 are not found outside Sundaland and wallacea, 385 (ca. 52% of the fauna) of which are single region endemics; the majority of these are actually single island endemics. Notes are provided on taxonomic problems or indicating problematic distribution records. Prodasineura lansbergei is considered to be a nomen nudum (stat nov.). For each of the eight main regions the history of the study of odonates is briefly discussed, information is provided on the coverage of the available data and the faunal composition is described. An overview is given of genera for which no larvae have been described. A brief comparison is made between the faunas of Sundaland and wallacea showing that they only share 10% of the species between them (76 of 743).